1947
DOI: 10.1002/cber.19470800106
|View full text |Cite
|
Sign up to set email alerts
|

Bakteriostatisch wirkende Nitro‐Verbindungen des Thiophens und Furans

Abstract: D a n n , M o l l e r . 23Nr. 1 p 4 7 J ders fur die Thiophenverbindungen IV und VIII, welche sowohl nach Art als auch Starke in ihrem Vermogen ortlich zu hetauben durchaus dem Anctsthesin (I) und Novokain (VI) entsprechen. Auch hemmt keiner der Ester das Wachstum von Streptobacteriuin plantarum in den verwendeten Konzentiationen bis 3 x lo-* g/ccm starker als die analogen Ester der p-Amino-benzoesiiure. Der Grund hierfiir konnte einerseits darin liegen, da13 die Affinitat zii den Haftstellen dieses Wuchsstoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1952
1952
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It has been suggested that nitrofurazone interferes with normal metabolism by virtue of its capacity to be reduced (15). In addition, previous authors have concluded from a study of nitrofurans, nitrothiophenes, nitrobenzenes, and related compounds, that ease of reducibility plays a major role in the antibacterial effectiveness of heterocyclic nitro compounds (16). These authors also proposed a relationship between the redox potential developed by the organism in culture and that required by the inhibitory nitrofuran, implying that interference with microbial reproduction was associated with formation of a reduction product (hydroxylamine) from the nitro compound (17).…”
Section: Resultsmentioning
confidence: 91%
“…It has been suggested that nitrofurazone interferes with normal metabolism by virtue of its capacity to be reduced (15). In addition, previous authors have concluded from a study of nitrofurans, nitrothiophenes, nitrobenzenes, and related compounds, that ease of reducibility plays a major role in the antibacterial effectiveness of heterocyclic nitro compounds (16). These authors also proposed a relationship between the redox potential developed by the organism in culture and that required by the inhibitory nitrofuran, implying that interference with microbial reproduction was associated with formation of a reduction product (hydroxylamine) from the nitro compound (17).…”
Section: Resultsmentioning
confidence: 91%
“…This is illustrated in Table 7, in which the activities of four pairs of nitro-and aminoimidazoles are compared. Dann & Moller (1947, 1949 had similarly observed that aminothiophenes and aminofurans were inactive. It is probable that the reactive forms of all of these drugs are partially reduced intermediates which are highly unstable ; likely candidates are the hydroxylamino-or nitroso-derivatives (Dann & Moller, 1949;Paul et al, 1960;McCalla et al, 1970).…”
Section: B P Goldstein and Othersmentioning
confidence: 99%
“…belongs to a class of drugs (including nitrofurans as well as nitroimidazoles) whose antimicrobial activity depends on the presence of the nitro group (Dann & Moller, 1947;Grunberg & Titsworth, 1973). Although members of this class of drugs differ in a number of properties including their spectrum of antimicrobial activity (Grunberg & Titsworth, 1973 ;Edwards, Dye & Carne, 1973)~ studies of the mechanism of action of nitrofurazone (McCalla, Reuvers & Kaiser, I 970), metronidazole (Ings, McFadzean & Ormerod, 1974) and MEV (Goldstein et al, 1977) suggest that the effective target of all of these drugs is DNA.…”
Section: -Methyl-2-nitro-~-vinylimidazole (Mev)mentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of [3H]nitrofuran into the cold trichloroacetic acid-insoluble fraction of intact cells. Nitrofuran [17 &g(3 ACi)] was used. For other details, see legend ofFig.…”
mentioning
confidence: 99%